THE PLACE AND IMPORTANCE OF CULTURAL ACTIVITY IN THE SOCIAL PROTECTION SYSTEM - Baxramova Nodira (International Journal of Literature and Language Studies, 2026)
The article analyzes the theoretical and legal foundations of the social protection system and the role of cultural activities within it. The study highlights modern trends in the development of social protection, its institutional and legal mechanisms, and the importance of cultural activities in social integration, rehabilitation, and human capital development. The findings indicate that cultural activities serve as one of the key factors in increasing the effectiveness of social protection systems.